Patient-centredness as a quality domain in Swedish healthcare: results from the first national surveys in different Swedish healthcare settings - Kandelaki, Ketevan (BMJ Open, 2016)
OBJECTIVES: Patients’ perception of the quality and patient-centredness of healthcare has gained increasing interest in the last decade in Sweden, as in other countries. The purpose of the study was to evaluate to what extent patients perceived Swedish healthcare as patient-centred and to explore the satisfaction levels related to gender, education level and to having or not having Swedish as one's mother tongue. DESIGN AND SETTINGS: This study has a cross-sectional design. Analyses were based on the first national patient surveys in Sweden, conducted between 2009 and 2010. The surveys included responses from 232 518 patients who had been in contact with primary, outpatient, inpatient, or emergency care units. Survey questions related to indicators of patient-centred care and sociodemographic variables were selected for the analysis. The patients’ level of satisfaction in the selected indicators was analysed and compared by sociodemographic and background factors. Multivariable logistic regression models were used for analysis. RESULTS: The patients expressed high levels of satisfaction in questions related to the ‘Respect’ indicator (81–96% satisfied) but lower levels in most of the other indicators of patient-centred care. Only 25–30% of the patients reported they had been told about possible warning signs of their condition or treatment and 58–66% said they had received enough information about their condition. Group differences were detected. The most satisfied patient groups were men, individuals with low levels of education and those with Swedish as their mother tongue. CONCLUSIONS: According to these first national patient surveys, achieving patient-centred healthcare for all citizens is a challenge for Swedish healthcare authorities. Future analyses of national patient surveys should show whether national efforts to encourage acceptance of patient-centred approaches and strategies for equal care will give intended results.